Management In A New Perspective (In Comparative Study Literature) - Hernawati W. Retno Wiratih; M. Havidz Aima; Alfadli Santowijaya; Hermanto Harun; Muhammad Ridwan (Greenation Research & Yayasan Global Resarch National, 2023)
Management Science has been in existence and evolving for about 3,000 years, spanning three distinct eras: prehistoric, historical, and modern. It's evident that knowledge of management is an integral part of human existence. In this article, we aim to introduce a novel perspective on Management, emphasizing the idea that effective management begins with self-mastery before extending to external management endeavors. The approach taken in this article involves merging established management theories with principles from the Alqur'an, Hadith, and works like